The M2 protein of live, attenuated influenza vaccine encodes a mutation that reduces replication in human nasal epithelial cells. Issue 48 (4th December 2017) - Wohlgemuth, Nicholas; Ye, Yang; Fenstermacher, Katherine J.; Liu, Hsuan; Lane, Andrew P.; Pekosz, Andrew
Abstract: The influenza A virus components of the live, attenuated influenza vaccine (LAIV) encode the HA and NA gene segments from a circulating virus strain and the remaining gene segments from the cold-adapted master donor virus, A/Ann Arbor/6/1960 (H2N2). The master donor virus imparts at least three phenotypes: temperature-sensitivity ( ts ), attenuation ( att ), and cold-adaption ( ca ). The genetic loci responsible for the att and ts phenotypes of LAIV were mapped to PB1, PB2, and NP by reverse genetics experiments using immortalized cell lines. However, some in vivo studies have demonstrated that the M segment, which acquired an alanine (Ala) to serine (Ser) mutation at M2 position 86 during cold adaption – a mutation found in no other influenza A virus strain - contributes to the att phenotype. Prior studies have shown this region of the M2 cytoplasmic tail to be critical for influenza virus replication. Using reverse genetics, we demonstrate that certain amino acid substitutions at M2 positions 83 and 86 alter the replication of influenza A/Udorn/307/72 (H3N2). Importantly, substitution of a Ser at M2 position 86 reduces A/Udorn/307/72 replication in differentiated primary human nasal epithelial cell (hNECs) cultures, but does not considerably affect replication in MDCK cells. When a Ser was substituted for Ala at M2 86 in LAIV, the virus replicated to higher titers and with faster kinetics in hNEC cultures, implicating this amino acid change as contributing to LAIV attenuation. Increased replication also resulted in increased production of IFN-λ. These data indicate the LAIV associated Ser mutation at M2 position 86 contributes to the att phenotype and is associated with a differential regulation of interferon in LAIV infection.